The Domain of Knowledge and Kampong Batik Laweyan at Surakarta City of Indonesia (Komunitas, 2022)
Kampong Batik Laweyan (KBL)  is one of the community heritage sites in Surakarta City of Indonesia. The KBL presents historical sites of Indonesia independent movement, batik home industries, and resources for tourist attractions such as kampong festivals, shopping arcade arrangements, and  art-deco homes’ architecture. The objective of this paper is to analyze the knowledge domain of the merchant community at Kampong Batik Laweyan (KBL), based on Wenger’s CoP theory. The method of research is qualitative. Data are collected through interview, observation and analyzed descriptively using analytical approaches. It is found that the KBL knowledge domain, for the heritage destination, is based on the merchant batik spirit and the history of the kampong.  The knowledge domain provides a shared context for members of the merchant community at KBL to enhance the  heritage tourist destination for community welfare of Surakarta. We recommend that the KBL might nurture its domain of knowledge, to help the community take into parts of the tourism destination at  Surakarta City.